Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Certainly! Let's solve the problem step-by-step to demonstrate that the distance between point [tex]\(O(2, 2)\)[/tex] and point [tex]\(A(5, 4)\)[/tex] is equal to the distance between point [tex]\(O(2, 2)\)[/tex] and point [tex]\(B(-1, 4)\)[/tex].
### Step-by-Step Solution:
#### (a) Calculate the distance [tex]\(OA\)[/tex] between points [tex]\(O\)[/tex] and [tex]\(A\)[/tex]:
Points:
[tex]\( O = (2, 2) \)[/tex]
[tex]\( A = (5, 4) \)[/tex]
The distance formula between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is:
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
Using the coordinates of [tex]\(O\)[/tex] and [tex]\(A\)[/tex]:
[tex]\[ OA = \sqrt{(5 - 2)^2 + (4 - 2)^2} \][/tex]
Calculate the differences:
[tex]\[ x\text{-difference} = 5 - 2 = 3 \][/tex]
[tex]\[ y\text{-difference} = 4 - 2 = 2 \][/tex]
Square these differences:
[tex]\[ x\text{-difference squared} = 3^2 = 9 \][/tex]
[tex]\[ y\text{-difference squared} = 2^2 = 4 \][/tex]
Add these squares and take the square root:
[tex]\[ OA = \sqrt{9 + 4} = \sqrt{13} \approx 3.605551275463989 \][/tex]
#### (b) Calculate the distance [tex]\(OB\)[/tex] between points [tex]\(O\)[/tex] and [tex]\(B\)[/tex]:
Points:
[tex]\( O = (2, 2) \)[/tex]
[tex]\( B = (-1, 4) \)[/tex]
Using the coordinates of [tex]\(O\)[/tex] and [tex]\(B\)[/tex]:
[tex]\[ OB = \sqrt{(-1 - 2)^2 + (4 - 2)^2} \][/tex]
Calculate the differences:
[tex]\[ x\text{-difference} = -1 - 2 = -3 \][/tex]
[tex]\[ y\text{-difference} = 4 - 2 = 2 \][/tex]
Square these differences:
[tex]\[ x\text{-difference squared} = (-3)^2 = 9 \][/tex]
[tex]\[ y\text{-difference squared} = 2^2 = 4 \][/tex]
Add these squares and take the square root:
[tex]\[ OB = \sqrt{9 + 4} = \sqrt{13} \approx 3.605551275463989 \][/tex]
#### (c) Compare the distances [tex]\(OA\)[/tex] and [tex]\(OB\)[/tex]:
We have:
[tex]\[ OA \approx 3.605551275463989 \][/tex]
[tex]\[ OB \approx 3.605551275463989 \][/tex]
Therefore, we can conclude:
[tex]\[ OA = OB \][/tex]
Hence, the distances from point [tex]\(O\)[/tex] to points [tex]\(A\)[/tex] and [tex]\(B\)[/tex] are equal.
### Step-by-Step Solution:
#### (a) Calculate the distance [tex]\(OA\)[/tex] between points [tex]\(O\)[/tex] and [tex]\(A\)[/tex]:
Points:
[tex]\( O = (2, 2) \)[/tex]
[tex]\( A = (5, 4) \)[/tex]
The distance formula between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is:
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
Using the coordinates of [tex]\(O\)[/tex] and [tex]\(A\)[/tex]:
[tex]\[ OA = \sqrt{(5 - 2)^2 + (4 - 2)^2} \][/tex]
Calculate the differences:
[tex]\[ x\text{-difference} = 5 - 2 = 3 \][/tex]
[tex]\[ y\text{-difference} = 4 - 2 = 2 \][/tex]
Square these differences:
[tex]\[ x\text{-difference squared} = 3^2 = 9 \][/tex]
[tex]\[ y\text{-difference squared} = 2^2 = 4 \][/tex]
Add these squares and take the square root:
[tex]\[ OA = \sqrt{9 + 4} = \sqrt{13} \approx 3.605551275463989 \][/tex]
#### (b) Calculate the distance [tex]\(OB\)[/tex] between points [tex]\(O\)[/tex] and [tex]\(B\)[/tex]:
Points:
[tex]\( O = (2, 2) \)[/tex]
[tex]\( B = (-1, 4) \)[/tex]
Using the coordinates of [tex]\(O\)[/tex] and [tex]\(B\)[/tex]:
[tex]\[ OB = \sqrt{(-1 - 2)^2 + (4 - 2)^2} \][/tex]
Calculate the differences:
[tex]\[ x\text{-difference} = -1 - 2 = -3 \][/tex]
[tex]\[ y\text{-difference} = 4 - 2 = 2 \][/tex]
Square these differences:
[tex]\[ x\text{-difference squared} = (-3)^2 = 9 \][/tex]
[tex]\[ y\text{-difference squared} = 2^2 = 4 \][/tex]
Add these squares and take the square root:
[tex]\[ OB = \sqrt{9 + 4} = \sqrt{13} \approx 3.605551275463989 \][/tex]
#### (c) Compare the distances [tex]\(OA\)[/tex] and [tex]\(OB\)[/tex]:
We have:
[tex]\[ OA \approx 3.605551275463989 \][/tex]
[tex]\[ OB \approx 3.605551275463989 \][/tex]
Therefore, we can conclude:
[tex]\[ OA = OB \][/tex]
Hence, the distances from point [tex]\(O\)[/tex] to points [tex]\(A\)[/tex] and [tex]\(B\)[/tex] are equal.
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.